Room‐Temperature Phosphorescence from a Series of 3‐Pyridylcarbazole Derivatives. Issue 71 (22nd November 2019) - Sasabe, Hisahiro; Kato, Yuki; Watanabe, Yuichiro; Ohsawa, Tatsuya; Aizawa, Naoya; Fujiwara, Wataru; Pu, Yong‐Jin; Katagiri, Hiroshi; Kido, Junji
Abstract: Exploration of pure metal‐free organic molecules that exhibit strong room‐temperature phosphorescence (RTP) is an emerging research topic. In this regard, unveiling the design principles for an efficient RTP molecule is an essential, but challenging, task. A small molecule is an ideal platform to precisely understand the fundamental role of each functional component because the parent molecule can be easily derivatized. Here, the RTP behaviors of a series of 3‐pyridylcarbazole derivatives are presented. Experimental studies in combination with theoretical calculations reveal the crucial role of the n orbital on the central pyridine ring in the dramatic enhancement of the intersystem crossing between the charge‐transfer‐excited singlet state and the locally excited triplet states. Single‐crystal X‐ray crystallographic studies apparently indicate that both the pyridine ring and fluorine atom contribute to the enhancement of the RTP because of the restricted motion owing to weak C−H⋅⋅⋅N and H⋅⋅⋅F hydrogen‐bonding interactions. The single crystal of the fluorine‐substituted derivative shows an ultra‐long phosphorescent lifetime ( τ P ) of 1.1 s and a phosphorescence quantum yield ( Φ P ) of 1.2 %, whereas the bromine‐substituted derivative exhibits τ P of 0.15 s with a Φ P of 7.9 %. We believe that this work provides a fundamental and universal guideline for the generation of pure organic molecules exhibiting strong RTP. Abstract : Room‐temperature phosphorescence from a series of 3‐pyridylcarbazole derivatives. The serendipitously discovered room‐temperature phosphorescence (RTP) of a novel series of simple 3‐pyridylcarbazole derivatives is presented. A long RTP lifetime of 0.15 s with a phosphorescent quantum yield of 7.9 % is achieved by the bromine‐substituted derivative. A significantly large spin–orbit coupling of 20.0 cm −1 between S1 and T6 is achieved by the n orbital and bromine atom on the pyridyl ring.